Optimization of Multi-Objective Mobile Emergency Material Allocation for Sudden Disasters - Li, Jianxun; Fu, Haoxin; Lai, Kin Keung; Ram, Bhagwat (Frontiers in Public Health, 2022)
The mobile emergency system is a new emergency mode that provides a solution to deal with the increasingly frequent sudden disasters by reasonably allocating mobile emergency facilities and optimizing the allocation of mobile emergency materials. We consider mobile emergency cost and mobile emergency time as two objective functions. This paper establishes a multi-objective mobile emergency material allocation model, and transforms the multi-objective. We choose the emergency material transportation path for coding, and apply the hybrid leapfrog algorithm for material allocation to obtain the optimal solution. Finally, the feasibility of the model is verified by taking Zhengzhou urban area under the "21.7" severe rainstorm and flood disaster in Henan Province. The result analyses show that the model can correspond to each stage of mobile emergency material allocation based on the value of cost preference, and put forward suggestions on the location of mobile emergency facilities and the amount of material allocation.